Albumin Macroaggregates labelled with Indium-113m for lung scintiscanning - Ciscato, V. A.; Nicolini, Jorge O.; Palcos, María Cristina (Northern Ireland, 1969)
Fil: Nicolini, Jorge O. Comisión Nacional de Energía Atómica; Argentina